2010
DOI: 10.1159/000320107
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Evaluation of Platelet and Leukocyte Activation and Interaction in a Rat Model of Pulmonary Arterial Hypertension

Abstract: Objectives: Thrombosis and inflammation are associated with the pathogenesis of pulmonary arterial hypertension (PAH). However, there are no solid data supporting the involvement of platelet and leukocyte activation and interaction in PAH. The present study thus investigated the activation and interaction of circulating platelets and leukocytes in a rat model of monocrotaline (MCT)-induced pulmonary hypertension. Methods: Mean pulmonary arterial pressure (mPAP) was monitored in rats (n = 24) before and 2, 3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Thus, homing of MSCs was only evident 1 week after cell transplantation. Interestingly, this is in agreement with the platelet activation kinetics in this PAH rat model; as we have previously shown, clear platelet activation only starts to emerge at least 1 week after MCT injection (14). Thus, it appears that MSC homing is correlated with platelet activation in vivo.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Thus, homing of MSCs was only evident 1 week after cell transplantation. Interestingly, this is in agreement with the platelet activation kinetics in this PAH rat model; as we have previously shown, clear platelet activation only starts to emerge at least 1 week after MCT injection (14). Thus, it appears that MSC homing is correlated with platelet activation in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…When vascular endothelium is injured, the coagulation system and the activation of platelets start simultaneously (7,24). We have also demonstrated an enhanced ex vivo platelet activation and platelet–leukocyte interaction in the rat model of PAH (14). Many studies have shown that activated platelets promote initial tethering, firm adhesion, migration, and differentiation of EPCs (6,21).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…[13] In fact, one of the typical pathological changes observed histologically in PAH is thrombosis in situ. The importance of platelets is highlighted by the fact that aspirin attenuates PAH in monocrotaline-treated rats by reducing plasma 5-hydroxytryptamine levels and increasing survival.…”
Section: Human Immunodeficiency Virus-associated Pulmonary Hypertensionmentioning
confidence: 99%